CONSTRUCTING LITERARY CANON METRICS FOR PEDAGOGICAL COMPETENCE - Fadli, Mohammad; Boeriswati, Endry; Rohman, Saifur (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
The term canon, derived from Ancient Greek kanon meaning “measuring rod,” evolved in modern European usage to denote rules or standards. Literary canonization refers to the selection and recognition of works deemed to belong to a distinguished category—frequently serving as benchmarks in educational and cultural institutions. Despite its institutional authority, the literary canon faces multiple challenges: it is a fluid, socially-constructed concept shaped by power dynamics, cultural norms, and institutional agendas. Critics point out its exclusionary tendencies, particularly its neglect of marginalized voices, and its resistance to evolving cultural values. This study interrogates canon as a socially mediated instrument—activated by networks of institutions, discourses, and elite agents—to evaluate how literary works are deemed “measurements of excellence” and the consequences for teaching. Canon, according to scholars like Vasari and Guillory, functions both as an aesthetic yardstick and as a form of cultural capital that shapes identity and selection in education. The findings underscore that canon is not a static benchmark but an “imaginary totality” continuously reshaped by institutional and ideological forces. Pedagogically, this calls for a more reflexive approach: educators should engage with canon critically, balancing its role in conveying cultural heritage with the need to incorporate diverse, pluralistic voices for more inclusive literary learning.